THE SYNERGETIC APPROACH IN PEDAGOGICAL DESIGN OF THE HIGHER SCHOOL EDUCATION ENVIRONMENT - Victor M. Kureychik; Veronika I. Pisarenko (Открытое образование (Москва), 2016)
The article is devoted to synergetics consideration as a basis of the new approach to design of the higher school education environment. Various approaches to the educational environment definition are analyzed. Application of seven main principles of synergetics in pedagogical sciences is analyzed and on their basis principles of designing of the educational environment of higher school are formulated. The model of the educational environment which can be used as a basis for designing of corresponding training system by the teacher of higher school is offered.